Особенности топологии поверхности слоистых кристаллов In₄Se₃ - Balitsky, A. A. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
The surface morphology of In₄Se₃ crystals has been investigated using scanning electron and tunneling microscopy. The surface shows virtually no relief fluctuations except for a cluster structure on the nanometer scale. After cleavage, a small number of extended defects of micrometer size were also detected on the surface. The surface roughness is practically ideal for the formation of sharp heterojunctions when used as a substrate.